Stargardt’s disease functionally – about the ways of coping with severe visual impairment - Kokot, Magdalena (Understanding Disability: Issues, Research, Reflections, 2021)
Visual disability affects about 2 million Poles. This group includes people who have been diagnosed with Stargardt’s disease. This disease occurs in the general population with a frequency of one in 10,000. It leads to legal blindness with visual acuity lower than 5%. Visual disturbances in this disease may occur in children, i.e. 7–12 years of age, as well as in adolescents and adults. People suffering from this disease experience a significant reduction in visual acuity, difficulty in recognizing colors, impaired depth vision, difficulties with accommodation, impaired central vision and often severe photophobia. The aim of the research was to collect information about the assistive technologies used by people with Stargardt’s disease and to identify their ability to move independently despite a significant reduction in visual acuity. The research results show that most of the 102 surveyed people use various types of assistive technology and experience significant visual impairment. At the same time, a significant part of this group declares that despite the inability to read the black print text, they can still move quite freely.